2012
DOI: 10.1158/0008-5472.can-12-1098
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Genomic Screen Identifies LDHB as an Essential Gene for Triple-Negative Breast Cancer

Abstract: Breast cancer has been redefined into three clinically relevant subclasses: (i) estrogen/progesterone receptor positive (ERþ/PRþ), (ii) HER2/ERRB2 positive, and (iii) those lacking expression of all three markers (triple negative or basal-like). While targeted therapies for ERþ/PRþ and HER2þ tumors have revolutionized patient treatment and increased lifespan, an urgent need exists for identifying novel targets for triple-negative breast cancers. Here, we used integrative genomic analysis to identify candidate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
140
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(154 citation statements)
references
References 46 publications
11
140
1
2
Order By: Relevance
“…However, we did not find that L-2HG levels correlated with transcript expression of hypoxiainducible lactate dehydrogenase A in these tumors, an enzyme that has been linked to hypoxia-related L-2HG production (41). Instead, L-2HG strongly correlated with lactate dehydrogenase B mRNA levels (ρ = 0.93, P < 0.01), which is an enzyme critical for the development of triple-negative tumors (43).…”
Section: +contrasting
confidence: 64%
“…However, we did not find that L-2HG levels correlated with transcript expression of hypoxiainducible lactate dehydrogenase A in these tumors, an enzyme that has been linked to hypoxia-related L-2HG production (41). Instead, L-2HG strongly correlated with lactate dehydrogenase B mRNA levels (ρ = 0.93, P < 0.01), which is an enzyme critical for the development of triple-negative tumors (43).…”
Section: +contrasting
confidence: 64%
“…LDHB has recently been shown to be a downstream target of mTOR critical for oncogenic mTOR-mediated tumorigenesis (54). It was also recently shown to be an essential gene in basal-like/triple-negative breast cancer metabolism (55). Proteomic analysis done by Cortesi et al (56) showed that high expression of the LDHB protein in tumor interstitial fluid was associated with response to chemotherapy in breast cancer patients, consistent with our results.…”
Section: Discussionsupporting
confidence: 88%
“…In preliminary studies, we found that BPLER are selectively sensitive to glycolysis inhibition. In fact, a recent study identified glycolysis as a selective TNBC dependency (McCleland et al, 2012). A recent chemical screen in HMLERshEcad identified the potassium ionophore salinomycin as a candidate drug (Gupta et al, 2009).…”
Section: Discussionmentioning
confidence: 99%